Ekonomi Politik Media: Isu Pemindahan Ibukota : (Analisis Framing dalam Media TVOne) - Abdillah, Robith (Program Studi Komunikasi dan Penyiaran Islam, Fakultas Dakwah, IAI Al-Qodiri Jember, 2022)
Government or presidential policy issues are always interesting to discuss. Moreover, the issue raised is a big issue like the one that a few weeks ago became very crowded. The issue of moving the capital is actually not a new issue in every presidential leadership. However, this issue re-emerged very rapidly considering that this issue does not seem to be just a discourse. This issue will reach the ears of the public through the mouths of the media that are so sweet. Various media reported with their respective styles and versions. This issue full of pros and cons has become very interesting for the media to discuss and make its own content. One of the media that is clever and shrewd in packaging this issue is TVOne media. TVOne media dares to be different from other media by presenting two camps that are pros and cons. This can then be categorized as the political economy of the media. How the media tries to commodify a content to produce economic coffers and adequate political power.